2001
DOI: 10.1136/oem.58.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Sensitisation to enzymes in the animal feed industry

Abstract: Objectives-To assess the prevalence of enzyme sensitisation in the animal feed industry. Methods-A cross sectional study was conducted in four animal feed factories, where several enzymes had been used in powder form for 7-9 years. Before this study, enzymes in liquid form had started to be used. Sensitisation to enzymes was examined by skin prick and radioallergosorbent (RAST) tests. Altogether 218 workers were tested; 140 people in various tasks in manufacturing, where exposure to various organic dusts and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…Our patient is the first reported case of allergic occupational asthma caused by the genetically engineered bacterial alpha‐amylase Termamyl®. Vanhanen et al [2001] reported on an individual who was sensitized to alpha‐amylase from another Bacillus species, Bacillus amyloliquefaciens. Several authors have described respiratory allergies caused by alpha‐amylase from the fungus Aspergillus oryzae [Baur et al, 1986; Houba et al, 1996; Nieuwenhuijsen et al, 1999; Vanhanen et al, 2001].…”
Section: Resultsmentioning
confidence: 99%
“…Our patient is the first reported case of allergic occupational asthma caused by the genetically engineered bacterial alpha‐amylase Termamyl®. Vanhanen et al [2001] reported on an individual who was sensitized to alpha‐amylase from another Bacillus species, Bacillus amyloliquefaciens. Several authors have described respiratory allergies caused by alpha‐amylase from the fungus Aspergillus oryzae [Baur et al, 1986; Houba et al, 1996; Nieuwenhuijsen et al, 1999; Vanhanen et al, 2001].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies11 13 17 have shown sensitising reactions with conjunctivitis, rhinitis, asthma or hypersensitivity pneumonitis. Most of the data have come from the detergent and food industries.…”
Section: Discussionmentioning
confidence: 97%
“…Sensitisation to enzymes in the animal feed industry has been estimated to be 7%. 9 Sensitisation to latex, a high potency allergen, in tappers and glove factory manufacture workers has been reported to range between 1.3% and 11% in four studies. 10 The reported sensitisation to grapes in the population studied is asymptomatic since none of the employees reported history of symptoms associated with anaphylaxis, contact urticaria, or oral allergy syndrome after grape consumption.…”
Section: Policy Implicationsmentioning
confidence: 99%